Cost-utility analysis of current COVID-19 vaccination program recommendations in Canada - Alison E. Simmons; Rafael N. Miranda; Michael W.Z. Li; Gebremedhin B. Gebretekle; Min Xi; Marina I. Salvadori; Bryna Warshawsky; Eva Wong; Raphael Ximenes; Melissa K. Andrew; Sarah Wilson; Matthew Tunis; et al. (Vaccine: X)
Background: As COVID-19 becomes established as an endemic disease with widespread population immunity, there is uncertainty about the economic benefit of ongoing COVID-19 vaccination programs. We assessed the cost-effectiveness of a COVID-19 vaccination program similar to current Canadian recommendations, modelled as annual vaccination for people aged less than 65 years with chronic medical conditions and biannual vaccination for adults aged 65 years and older. Methods: Using a static individual-based model of medically attended COVID-19 in a population of one million people, we estimated costs (in 2023 Canadian dollars), quality-adjusted life years (QALYs), and incremental cost-effectiveness ratios (ICERs). We used health system and societal perspectives and a 1.5 % discount rate. Parameters were based on recent COVID-19 epidemiology, vaccine characteristics, and costs. Results: Between July 2024 and September 2025, a program similar to current Canadian recommendations was estimated to avert 3.1 % (95 % credible interval (CrI): 3.0 to 3.2 %) of outpatient cases, 8.8 % (95 % CrI: 7.3 to 10.4 %) of inpatient cases, 3.6 % (95 % CrI: 2.8 to 4.3 %) of PCC cases, and 9.4 % (95 % CrI: 5.6 to 13.8 %) of deaths compared to no vaccination. The number needed to vaccinate to prevent one hospitalization and one death was 1121 (95 % CrI: 941 to 1357) and 8656 (95 % CrI: 5848 to 14,915), respectively. For the health system perspective, the program would cost an additional $4.695 million but result in 221.17 QALYs gained, leading to an ICER of $21,227 per QALY compared to no vaccination. Vaccine price influenced cost-effectiveness, with higher prices reducing the likelihood the program met common cost-effectiveness thresholds. Conclusions: A program similar to current COVID-19 recommendations in Canada is likely effective and cost-effective compared to no vaccination. However, unlike some other research studies, alternate vaccination strategies that may offer better value for money were not evaluated.